Desmoglein 2 is a receptor for adenovirus serotypes 3, 7, 11, and 14 - Wang, Hongjie (2010)
We have identified desmoglein 2 (DSG2) as the primary high-affinity receptor used by adenovirus (Ad) serotypes Ad3, Ad7, Ad11, and Ad14. These serotypes represent important human pathogens causing respiratory tract infections. In epithelial cells, adenovirus binding to DSG2 triggers events reminiscent of epithelial-to-mesenchymal transition, leading to transient opening of intercellular junctions. This improves access to receptors, e.g. CD46 and Her2/neu, that are trapped in intercellular junctions. In addition to complete virions, dodecahedral particles (PtDd), formed by viral penton and fiber in excess during viral replication, can trigger DSG2-mediated opening of intercellular junctions as shown by studies with recombinant Ad3 PtDd. Our findings shed light on adenovirus biology and pathogenesis and have implications for cancer therapy.